OPERA: responses to peginterferon and ribavirin therapy in a subgroup of interferon‐naïve patients with HIV/HCV genotype 2/3 co‐infection in Italy. (11th August 2014) - Bruno, Raffaele; Cariti, Giuseppe; Nasta, Paola; Capetti, Amedeo; Ravasio, Veronica; Galli, Massimo; Raise, Enzo; Palmieri, Giulio; Iannacone, Claudio; Puoti, Massimo
Abstract Background & Aims Hepatitis C virus (HCV) genotype 3 (G3) is common among HIV/HCV co‐infected individuals and associated with moderate sustained virological response (SVR) rates with pegylated interferon (PEG‐IFN) plus ribavirin (RBV) therapy, while G2 is less frequent and associated with higher SVR. To determine SVR and other response rates, identify SVR predictors and analyse differences between G2 and G3 with PEG‐IFN/RBV in a large HIV/HCV G2/3 patient population. Methods This subgroup analysis of the prospective, observational OPERA (Optimized Pegylated interferon Efficacy and anti‐Retroviral Approach) study was conducted between 2005 and 2011 in Italy in PEG‐IFN/RBV‐naïve HIV/HCV patients. The primary efficacy endpoint was SVR rate (HCV RNA <50 IU/ml or undetectable 24 weeks after end‐of‐treatment). Results Five hundred and fifty‐six HCV G2/3 patients (G2 n = 60; G3 n = 496) were treated with PEG‐IFN alfa‐2a 180 μg/week or PEG‐IFN alfa‐2b 1.5 μg/kg, + RBV 13.6 ± 2.3 (mean ± SD) mg/kg/day for median 47 (26–54) weeks. SVR rates were 57.7%, 68.3% and 56.5% for G2/3, G2 and G3 respectively) and RVR rates were 53.2%, 57.1% and 45.8% respectively. Independent SVR predictors were undetectable baseline HIV RNA [adjusted odds ratio (AOR), 2.64; 95% CI: 1.523–4.565, P = 0.0005], age (AOR 0.95 per year; 95% CI: 0.908–0.994, P = 0.0258) and anti‐HCV treatment duration (AOR 1.034 per week; 95% CI: 1.013–1.057, P = 0.0019). Conclusions Undetectable HIV RNA, longer anti‐HCV treatment adherence and younger age were independent SVR predictors in treatment‐naïve HIV/HCV G2/3 patients receiving PEG‐IFN/RBV. Suppressing HIV RNA replication before anti‐HCV therapy and increasing adherence to PEG‐IFN/RBV treatment SVR rates may improve SVR.